Vitamin and mineral supplementation and neuromuscular recovery after a running race - Gauche, E.; Lepers, R.; Rabita, G.; Leveque, J. M.; Bishop, D.; Brisswalter, J.; Hausswirth, C. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This double-blind study investigated the effects of vitamin and mineral complex supplementation on the neuromuscular function of the knee-extensor muscles after a prolonged trail running race.